2016
DOI: 10.18632/oncotarget.7045
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perioperative probiotics treatment for colorectal cancer: short-term outcomes of a randomized controlled trial

Abstract: This study was designed to mainly evaluate the anti-infective effects of perioperative probiotic treatment in patients receiving confined colorectal cancer (CRC) respective surgery. From November 2011 to September 2012, a total of 60 patients diagnosed with CRC were randomly assigned to receive probiotic (n = 30) or placebo (n = 30) treatment. The operative and post-operative clinical results including intestinal cleanliness, days to first - flatus, defecation, fluid diet, solid diet, duration of pyrexia, aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(121 citation statements)
references
References 34 publications
4
114
0
3
Order By: Relevance
“…The prophylactic probiotics were mostly Lactobacillus (10/14) and Bifidobacterium (12/15) based, while the preoperative antibiotics prophylaxis regimens varied across studies. Despite all studies performed mechanical bowel preparation, only one study applied oral antibiotics, one study applied both oral and intravenous infusion of antibiotics, and most of the studies used intravenous infusion of cephalosporins plus metronidazole, one used intravenous infusion of gentamicin plus metronidazole, and three studies used intravenous infusion of cephalosporins alone . Most trials conducted power calculation (13/14), many did not apply intention‐to‐treat analysis (11/14) …”
Section: Resultsmentioning
confidence: 99%
“…The prophylactic probiotics were mostly Lactobacillus (10/14) and Bifidobacterium (12/15) based, while the preoperative antibiotics prophylaxis regimens varied across studies. Despite all studies performed mechanical bowel preparation, only one study applied oral antibiotics, one study applied both oral and intravenous infusion of antibiotics, and most of the studies used intravenous infusion of cephalosporins plus metronidazole, one used intravenous infusion of gentamicin plus metronidazole, and three studies used intravenous infusion of cephalosporins alone . Most trials conducted power calculation (13/14), many did not apply intention‐to‐treat analysis (11/14) …”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, the present study evaluated the prophylactic and therapeutic effects of probiotics on patients with CRC in the pre-and postoperative, and at the same time searched for preventive strategies from recent experimental models. A large number of studies have shown that probiotics can prevent the initiation or development of cancer by changing the intestinal microbial composition, host protection against pathogenic bacteria and fungi, the production of biological substances such as short-chain fatty acid and conjugated linoleic acid, inactivation of carcinogenic compounds, improvement of gut barrier function, modulation of immune responses, apoptosis, anti-proliferative effects and antioxidant activity (21)(22)(23) (18) observed better outcomes by using these microorganisms in the therapeutic intervention for patients with CRC. Perioperative administration of probiotics reduces the inflammatory response, which can lead to a reduction in length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 4 of 6 articles evaluated showed a positive response of the probiotic use (4,5,9,18), while 2 of them showed a placebo response (2,19).…”
Section: Detection Of Bacteria In Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…O uso de probióticos e prebióticos diminui o risco de complicações pós-operatórias, como septicemia 22,28 , ventilação mecânica, infecções, pneumonia e vazamento da anastomose 25,26 , além de trazer benefícios clínicos em curto prazo através da recuperação mais rápida da função intestinal, com menor incidência de diarreia e alta hospitalar mais rápida 26,30 . Além disso, o uso de probióticos e prebióticos auxilia na manutenção da resistência à colonização microbiana por microrganismos indesejáveis e restringe a translocação bacteriana no intestino.…”
Section: Discussionunclassified